Model of strategies in developing Islamic thought through curriculum: a study of Sumatra Thawalib - Muh Saerozi (IAIN Salatiga, 2014)
This paper describes the models of strategies for developing of Islamic thoughtsthrough curriculum discovered by Sumatera Thawalib. Sumatera Thawalib isthe study centre of development of Islamic thought in Sumatera. The studyuses a historical approach and covers the history during 1900 to 1942. Thestudy centre is well known as part of modern Islamic movement. However, itsstrategy in thought development is not linear with the strategy of modernIslamic movement. In practical, Thawalib is in line with the model of neomodernstrategy. The developing of Thawalib Islamic thought does not necessarilylead Thawalib scholars to invalidate the works of classical scholars. However,the thought leads them to appreciate and posits the works of classicalscholars as a guidance to scaffold students’ thought to be more rational anddynamic. Thawalib strategy has proven that it gives significant contribution tothe development of reforming Islamic thought in Indonesia.Makalah ini menjelaskan model strategi untuk mengembangkan pemikiranIslam melalui kurikulum yang dikembangkan oleh Sumatera Thawalib.Sumatera Thawalib adalah pusat studi pengembangan pemikiran Islam diSumatera. Penelitian ini menggunakan pendekatan historis dan mencakupsejarah selama 1900 sampai 1942. Organisasi ini dikenal sebagai bagian darigerakan Islam modern. Namun, strategi dalam pengembangan pemikiran tidaklinier dengan strategi gerakan Islam modern. Dalam praktek, Thawalib inisejalan dengan model strategi neo-modern. Perkembangan Thawalib dalampemikiran Islam tidak selalu membawa para ulama Thawalib untuk membatalkankarya ulama klasik. Namun, pikiran itu membuat mereka menghargai danberpendapat bahwa karya-karya ulama klasik dapat dijadikan sebagai pedomanpemikiran siswa agar menjadi lebih rasional dan dinamis. Strategi Thawalibtelah membuktikan bahwa hal itu memberikan kontribusi yang signifikanterhadap perkembangan reformasi pemikiran Islam di Indonesia.